Continuous wavelet transform of railway track defectoscopic signals in the Matlab Wavelet Toolbox - Vitalij Nichoga; Liubomyr Vashchyshyn (Biuletyn Wojskowej Akademii Technicznej, 2014)
[b]Abstract[/b]. Rail networks across the world are getting busier with trains travelling at higher speeds and carrying more passengers and heavier axle loads than ever before. The combination of these factors has put considerable pressure on the existing infrastructure, leading to increased demands in inspection and maintenance of rail assets [1]. Nowadays, rails are systematically inspected for internal and surface defects using various non-destructive evaluation (NDE) techniques, the most common of which are ultrasonic and magnetic flux leakage (MFL) methods. The article is focused on the analysis of defectoscopic signals received using the magnetic wagon-defectoscope of Lviv Railway (MFL method) by the continuous wavelet transform (CWT).[b]Keywords[/b]: rail, crack, CWT